Piastowie i ich święty, rzymski protektor - Wetesko, Leszek (Ecclesia. Studia z Dziejów Wielkopolski, 2011)
The author links the spreading of the cult of St. Peter on the Piast lands with the specific political-cultural situation of the newly emerging state organism. It was a situation when the choice of an appropriate patron was in fact a tactic measure with far reaching consequences. The article presents a logical sequence of historical developments which would eventually lead to entrusting the state to the protection of this special saint. The author also mentions the active cult of the saint and focuses on the image of the sword of St. Peter, referring in this context to a miniature from the „Gniezno Codex” with a representation of the scene in the Garden of Olives.